COMENTARIO DEL LIBRO: Díaz, D. y Molina, I. (ed.). (2018). La inolvidable edad. Jóvenes en la Costa Rica del siglo XX. Costa rica: editorial Universidad nacional. - Cerdas Albertazzi, Jose Manuel (2018)
Review